2017
DOI: 10.1002/adem.201600859
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Crystallography of α Phase Nucleated Dynamically during Thermo‐Mechanical Treatments in Metastable β Titanium Alloy

Abstract: The a phase nucleated dynamically during the thermo-mechanical coupling process in titanium alloy is really interesting but difficult to sufficiently ascertain. In the present work, the a phase nucleation behavior, the orientation relationship between a/b as well as the phase transformation kinetics during hot deformation of Ti-5553 alloy were investigated in-depth. Results reveal that the "necklace" microstructure formed. The Burgers orientation relationship between a/b phases has been destroyed gradually. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…Compared with the results of high temperature deformation at 800°C in Ref. [38], there is no significant change in the deformation mechanism of Ti-5553 alloy.…”
Section: Slip Drv/drx and Globularizationcontrasting
confidence: 55%
See 1 more Smart Citation
“…Compared with the results of high temperature deformation at 800°C in Ref. [38], there is no significant change in the deformation mechanism of Ti-5553 alloy.…”
Section: Slip Drv/drx and Globularizationcontrasting
confidence: 55%
“…Furthermore, the dislocation slip systems are controlled by thermally-activated process. That is why dislocation slip is the predominant hot deformation mode in metastable β titanium alloys, whether deformation at the high temperature (for example 800°C [38]) and lower 600°C) or room temperature. The slip as a predominant deformation mechanism was also observed in other Ti-alloys by S. Hanada et al [40].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Their results indicated that the deformation bands and dislocations generation during the thermal deformation process increased the nucleation sites of α phase and promoted the β→ α transition. Fan et al (2017) explained the spheroidization mechanism of α phase of Ti-7333 alloy during thermal deformation. However, Jonas et al (2017) found that flow stress reached a peak after thermal deformation and then decreased gradually, and the content of β phase increased.…”
Section: Introductionmentioning
confidence: 98%
“…Titanium and its alloys have a wide range of applications, including aerospace, biomedicine and transportation industries, due to their excellent mechanical properties [1][2][3]. The microstructure is a key factor determining the mechanical properties [4,5]. It is well known that the lamellar microstructure of titanium alloy has moderate strength and fatigue crack growth resistance but low ductility, while the equiaxed microstructure presents a better balance of strength and ductility [6].…”
Section: Introductionmentioning
confidence: 99%